Great Expectations? A Systematic Review of the Relationship Between the School-to-Higher Education Transition and Social Mobility. Issue 4 (4th July 2019) - Mocca, Elisabetta; Rojon, Céline; Hernández, Javier
Abstract: Education has always been considered as a means for social mobility, leveling off inequalities among individuals and enabling them to realize their potential. Against a backdrop dominated by political discourses on employability, flexibility and performance, there are growing concerns that students' career decisions may be affected by individual and structural factors undermining the fairness of the transition from school to higher education (HE). To address this issue, this article seeks to unpack the enablers and barriers affecting the school-to-HE transition. To do so, we undertook a systematic review of papers published in psychology, sociology, education and public policy from 1985 to date, a period where major employment and education reforms in advanced and emerging economies were implemented. The findings show that socio-economic, cultural and institutional factors affect students' access to HE. By taking stock of research on the school-to-HE transition, this article contributes to broaden the debate on the topic and reflects upon the relation between education and social mobility.